Nobuli: A chatbot for tackling cyberbullying among youngsters - Tan, Mei Jun (2022)
Cyberbullying is increasing at an alarming rate not only in Malaysia, but globally. The increase of cyberbullying could be directly related to the increase of users on the internet and the increase in time spent online which could be due to the Covid-19 pandemic. Governments, schools, and parents have been voicing out their concerns in relation to cyberbullying as the most vulnerable group to be victimized by cyberbullying would be youngsters. Youngsters who are also known as teenagers are mostly school students who lack the education and awareness on the context of cyberbullying in general and might even take up the role as a cyberbully without themselves being aware of their actions or on the other hand, end up being a victim of cyberbullying. Hence, this project involved the development of a chatbot known as Nobuli which is a chatbot to tackle cyberbullying among youngsters and the Nobuli chatbot is integrated into a mobile application. The objectives of this project are (i.) to investigate the implementation of Natural Language Processing (NLP) to detect cyberbullying in chatbots, (ii.) to design a chatbot in a mobile application on cyberbullying and (iii.) to evaluate the effectiveness of chatbot in increasing the cyberbullying awareness among youngsters using functional testing and user acceptance testing. The developed Nobuli chatbot and Nobuli mobile application are developed using the Agile software development methodology consisting of seven phases and there are a total of five modules implemented which includes the About Cyberbullying module, the Nobuli Chatbot module, the Quiz module, the News module and the Report module. After the entire Nobuli mobile application has been developed with the modules implemented, the Nobuli mobile application is tested using functional testing and user acceptance testing. Overall, the chatbot would be expected to educate, spread awareness, and persuade youngsters to report cyberbullying cases which will contribute to a decrease in cyberbullying cases in the future.